ANALYSIS OF PREVENTIVE MAINTENANCE AND CORRECTIVE MAINTENANCE USING RELIABILITY ANALYSIS AND FMEA (FAILURE MODES AND EFFECTS ANALYSIS) - Aji, Muhammad Dava; Abdurahman, Zaki; Azizah, Nabila Aulia; Annisa, Putri Dwi (Journal of Industrial Engineering Management, 2024)
In maintaining the condition of the machine so that it does not experience damage or at least to reduce the type of damage, a good and appropriate machine maintenance system is needed so that the results can increase the effectiveness of the machine and reduce losses resulting from engine damage. Reliability and availability greatly affect the performance of a system and equipment used, the operating process, and the expertise of the operator in running the machine. Maintenance or maintenance is often associated as the root of reliability, therefore, there is a need for a good maintenance strategy to increase the reliability of a production system. At PT. XYZ factors that affect production bottlenecks are system or equipment failures and scheduling that is not in accordance with the planned production time and downtime that occurs can affect many things including cost, time, reliability guarantees and others. This research involves the use of mathematical methods through reliability analysis and analysis of potential and impact failures, with the aim of optimizing corrective and preventive handling to minimize repair costs and reduce unnecessary costs.